Climate Variability and the Resilience of Smallholder Tea Production in the East Usambara Mountain Farming System, Tanzania - Ally Juma Mkumbukiy; Sang-Min Han; Amos Joel Makweta (MultiTech Publisher, 2024)
The complexities of climate change are well-known, and it has immediate and long-term consequences on the environment and natural resources. This global concern adversely affects sustainable development sectors and economic systems including the agricultural sector. The tea sector is among the largest export crops contributing to earnings and revenues. Its production has been declining, and the reasons behind this decline remain unclear. This study proposed to explore the influences of climate variability on the current productivity trend of smallholder tea farmers in Tanzania. The study involves quantitative data analysis, collected from 1990 to 2020 including monthly precipitation, temperature statistics, and Greenleaf production gathered as secondary data from the Tea Research Institute of Tanzania and the Tea Board of Tanzania. The study found that rainfall and temperature change significantly influence smallholder farmers' tea production in the East Usambara Mountains. The optimal climate elements (temperature and precipitation) positively improve smallholder farmers' tea production. In contrast, extreme climate variability triggers negative effects on tea production when precautions and adaptation measures are not considered. To summarize, it is recommended that farmers engage in different programs and training sessions to enhance their perception and adaptability to climate change.